Plan de negocios para la creación de una distribuidora de zapatos de marcas nacionales e internacionales en el cantón El Empalme, año 2013 - Cevallos Acebo, Natalia Guadalupe (2015)
The project is located in the propositional paradigm within the feasible reality-oriented mode of installation and commissioning for the purposes required in the distribution of national and international footwear brands, located in El Empalme Canton province of Guayas. The project with the objective: Evaluate the dealer shoe market to determine the feasibility of creating a footwear distributor. This research is descriptive design, developed with technical excellence. Implementation with primary sources of high quality technological process for observing the product quality through the application of a survey type questionnaire conducted among residents of Empalme Canton. The results of the investigation determined the wide demands related to the distribution of shoes and their quality. For that, the investment required for this present project is $ US $ 120,000.00 funded by the National Finance Corporation CFN. The calculations and financial analysis during the investigation, the feasibility of the project was achieved, the profitability of the company in its first fiscal year, net income of $ 39.960,59 is obtained from the second year of operations to grow by 6%, as detailed in the table of cash flows; the NPV of the project is $ 293.901,82 internal rate of return IRR is 28%, economic indicator that determines market exploitation exclusive offer national and international footwear brands like business is justified, means that the implementation proposal, the company will achieve the objectives. 1